Geografia da mortalidade no trânsito no Brasil - Bastos, Jorge Tiago; Ferraz, Antonio Clóvis Pinto; Vieira, Heitor; Bezerra, Barbara Stolte [UNESP] (My University, 2012)
In road safety studies that involve accidents comparisons in distinct geographical spaces or in different periods of time in the same geographical space, the index which lists the number of traffic fatalities with the distance traveled by road transport vehicles is considered more appropriate than the rates related to the population or the fleet. In this paper, the results of an original research are presented, in which the values of the rate of traffic deaths per billion kilometers traveled (IMBQ) by the motor vehicle fleet in Brazil and in each state of the country were estimated. The evaluation was performed based on the official number of fatalities provided by the Ministry of Health and on the amount of fuel sold informed by the National Agency of Petroleum, Natural Gas and Biofuels. In 2009, Brazil presented an index of 52.84 fatalities per billion kilometers, which reveals an extremely alarming situation considering that this value is from 7 to 12 times higher than the one for more developed countries. An important correlation between the death index in the states and the Gross Domestic Product (GDP) per capita was observed; in general, the less economically developed is the state, it means, lowest GDP, higher is the IMBQ.

Nos estudos de segurança no trânsito que envolvem a comparação da acidentalidade em distintos espaços geográficos ou em períodos de tempo diferentes no mesmo espaço geográfico, o índice que relaciona o número de mortes no trânsito à quilometragem percorrida pelos veículos de transporte rodoviário é considerado mais adequado que as taxas que utilizam como referência a população ou a frota de veículos. Neste artigo são apresentados os resultados de pesquisa inédita, na qual foram estimados os valores do índice de mortes em acidentes de trânsito por bilhão de quilômetros percorridos (IMBQ) pela frota de veículos motorizados para o país e para cada estado. A avaliação foi feita com base no número oficial de mortes registradas pelo Ministério da Saúde e na quantidade de combustível vendida informada pela Agência Nacional do Petróleo, Gás Natural e Biocombustíveis. Em 2009, o Brasil apresentou um índice de 52,84 mortes por bilhão de quilômetro, o que reflete uma situação extremamente grave considerando ser esse valor entre 7 e 12 vezes maior que nos países mais desenvolvidos. Uma significativa correlação entre o índice de mortes nos estados e o Produto Interno Bruto (PIB) per capita foi observada; em geral, quanto menos desenvolvido economicamente o estado, ou seja, menor o PIB per capita, maior o IMBQ.
Geography of traffic fatalities in Brazil
Keywords: Traffic fatalities; Distance traveled; Death index; Mortalidade no transito; Quilometragem percorrida; Índice de mortes